2017
DOI: 10.21608/jppp.2017.46376
|View full text |Cite
|
Sign up to set email alerts
|

Population Density of Piercing-Sucking Pests and their Associated Natural Enemies on Pepper, Capsicum annuum L. Plants under Greenhouse Condition at Ismailia Governorate, Egypt

Abstract: This study was conducted on pepper plants, Capsicum annuum L under greenhouse condition, in the farm of El Qassaseen Horticulture Research Station, Ismailia Governorate during the two successive winter seasons of 2013/2014 and 2014/2015 to survey the main piercing-sucking pests and associated natural enemies, also determine the population density and occurrence percentage for main species of pests and associated natural enemies. The obtained results showed that, the homopterous insects were the dominant pierci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Our findings were nearly comparable to those obtained by Al-Habshy et al (2019) who reported that leafhopper and aphid peaks occurred in 3 rd week of February on barley plants. Also on pepper, the highest peak of aphid species was 165.67 individuals /plant in mid-March (Ibrahim, 2017). In the present study, the infestation of all tested pests was recorded with 1-3 peaks as in the direction of the findings by El-Hadary and Ahmed (2021) who detected four peaks with A. gossypii, two peaks with B. tabaci and three peaks with Empoasca spp.…”
Section: -Population Fluctuation Of Certain Piercing-sucking Pests On...supporting
confidence: 80%
See 1 more Smart Citation
“…Our findings were nearly comparable to those obtained by Al-Habshy et al (2019) who reported that leafhopper and aphid peaks occurred in 3 rd week of February on barley plants. Also on pepper, the highest peak of aphid species was 165.67 individuals /plant in mid-March (Ibrahim, 2017). In the present study, the infestation of all tested pests was recorded with 1-3 peaks as in the direction of the findings by El-Hadary and Ahmed (2021) who detected four peaks with A. gossypii, two peaks with B. tabaci and three peaks with Empoasca spp.…”
Section: -Population Fluctuation Of Certain Piercing-sucking Pests On...supporting
confidence: 80%
“…Many phytophagous pests including cotton whitefly, Bemisia tabaci, aphids, Aphis gossypii & Myzus persicae, leafhopper, Empoasca decipiens and two-spotted spider mites, Tetranychus urticae were infested Solanaceae and Cucurbitaceae crops (Abd El-Wahab et al, 2012 andAl-Habshy et al, 2013). A large scale of these sucking pests attack numerous Cucurbitaceae and Solanaceae species such as watermelon (Abou El-Saad, 2015) cucumber (Ibrahim, 2017), ash-gourd (Khan et al, 1999), squash (Abdallah et al, 2012), cantaloupe (Younes et al, 2010) snakecucumber (Mondal et al, 2020) pepper (Havanoor and Rafee, 2018) and eggplant (Helmi and Rashwan, 2015). In addition to the direct infestation of piercing-sucking insects, which causes the transmission of viral disease to these plant families, as well as the secretion of honeydew, which leads to the growth of black mold, also, causing photosynthesis stop (Ghosh et al, 2019 andKazak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Numbers of aphidophagous adults that visually counted in peach trees that harboured the green peach aphid, M. persicae colonies during the first ( 2019 Ibrahim (2017) in Egypt recorded 3-4 peaks of abundance for M. persicae on pepper. In addition, he recorded two peaks for Coccinella spp.…”
Section: Seasonal Occurrence Of Aphidophagous Adultsmentioning
confidence: 99%
“…(i.e. mummified aphids) during 2019/2020 (A) and 2021/2021 (B) seasons at Aga district Ibrahim (2017). in Egypt recorded 3-4 peaks of abundance for M. persicae on pepper.…”
mentioning
confidence: 99%